PATH-17. INCREASING VALUE OF AUTOPSIES IN PATIENTS WITH BRAIN TUMORS IN THE MOLECULAR ERA. (5th November 2018) - Ahrendsen, Jared; Filb n, Mariella; Chi, Susan; Manley, Peter; Wright, Karen; Bandopadhayay, Pratiti; Kieran, Mark; Jones, Robert; Ligon, Keith; Alexandrescu, Sanda
Abstract: INTRODUCTION: Many pediatric brain tumors are associated with high morbidity and mortality, which is due to insufficient understanding of tumor biology. Limited tissue allocation for research from small surgical specimens is a key barrier to improved understanding but brain tumor autopsies have been a valuable resource. This study reviews the brain tumor autopsy practice at our institution, and describes emerging research ultilization patterns beyond the clinical autopsy report. METHODS: Brain tumor autopsies in the interval 2007–2017 were identified, and we analyzed the method of tissue triaging for research and documented its specific uses. RESULTS: Of 1602 deaths at Boston Children's Hospital (636 with autopsies), 96 had a diagnosis of brain tumor (56 consented for autopsy, ). Diffuse intrinsic pontine glioma (DIPG) and other high-grade gliomas accounted for the greatest proportion of diagnoses (52% of brain tumor autopsies). The tumors that resulted in the highest number of autopsies were DIPGs (25 deaths, 21 autopsies). Other frequent diagnoses were atypical teratoid rhabdoid tumors (13 deaths, 8 autopsies) and medulloblastomas (12 deaths, 3 autopsies). Fourteen DIPGs (56%) had tissue samples contributed to the DIPG registry consortium. Mapping was performed on 20 DIPG tumors in order to study heterogeneity; ten underwent whole genome sequencing, RNA expression studies and arrayCGH. Cell lines were successfully generated from 2 DIPGs and 1 ATRT (attempted on 12 autopsies) that had a post-mortem interval of less than 8 hours. CONCLUSIONS: Our institutional pediatric brain tumor autopsy experience demonstrates the increasing utility of autopsy-derived tissue for multiple types of research. Our experience demonstrates a wide utilization of brain tumor autopsy material in translational research, and might encourage research consent for brain tumor autopsy and active collection of unfixed autopsy material in the molecular era.